Toxic masculinity men, meaning, and digital media - McGlashan, Mark; Mercer, John 1966- (Masculinity, sex,and popular culture, 2023)
"Toxic Masculinity brings together scholars across disciplines to explore the ways in which toxic masculinity is constructed, configured, and represented online. What is 'toxic masculinity'? Examining what it means in the media and public discourse, the contributors have explored a constellation of behaviours, cultures, and practices that have been labelled as (or associated with) toxic masculinity including those of politicians, extremists, incels, as well as individual 'ordinary' men and their everyday behaviours. Topics covered in the collection include: Incels and MGTOW, bro culture, sexual violence, internalised homophobia, transphobia, white masculinity, and political discourse. Toxic Masculinity is intended for a broad spectrum of gender, media, cultural, and masculinity studies professionals, academics, researchers, and students. The book also includes suggestions for further reading, a discussion of methods used in each"--